Genome-wide association study identifies novel genes for plant architecture and yield traits in cassava (Manihot esculenta Crantz) - Olayinka, Abiodun Fatai; Dzidzienyo, Daniel Kwadjo; Mbanjo, Edwige Gaby Nkouaya; Offei, Samuel Kwame; Tongoona, Pangirayi Bernard; Danquah, Eric Yirenkyi; Egesi, Chiedozie; Rabbi, Ismail Yusuf (Frontiers in Plant Science, 2025)
Cassava (Manihot esculenta Crantz) cultivars with compact plant types and moderate plant heights are required for mechanical farming to boost productivity. Plant architecture is a complex trait controlled by environmental and genetics factors. However, little is known about the genetic basis of cassava plant architecture. This research sought to bridge the knowledge gap by elucidating the genetic basis of traits related to plant architecture, yield, and productivity in cassava. A panel of 453 cassava clones developed at the International Institute of Tropical Agriculture was genotyped using two distinct genotyping platforms: low-density DArTseq and DArTag. Plant architecture, yield, and productivity-related traits were evaluated at three locations across two growing seasons in Nigeria. Following data filtering, 420 clones, 54,574 DArTSeq, and 2,527 DArTag single-nucleotide polymorphism (SNP) markers were used for genome-wide association studies (GWAS). Of the 16 SNPs identified by GWAS using DArTSeq markers, only one was detected during validation, and the remaining SNPs may be false positives. Sixteen SNPs were found to be significant using DArTag markers. Fifteen of these were associated with 21 putative candidate genes for five plant architecture traits (17 genes) and three yield traits (four genes). Six of the identified candidate genes were novel. The identified candidate genes were associated with various metabolic processes, including plant architecture, adaptation, root development, plant growth, and stress response. The limited number of significant markers identified using DArTSeq markers could be explained by the large gaps and uneven marker distribution observed across the genome with the DArTseq platform compared to DArTag. The findings of this study provide new insights into the genetic basis of plant architecture and yield in cassava. Cassava breeders could leverage this knowledge to optimize plant architecture and yield in cassava through marker-assisted selection and targeted manipulation of candidate genes.